International exposure : perspectives on modern European pornography, 1800-2000 - Sigel, Lisa Z., 1965- (New Brunswick, N.J. : Rutgers University Press, 2005)
International Exposure demonstrates the wealth of desires woven into the fabric of European history: desires about empire and nation, about self and other, about plenty and dearth. By documenting the diverse meanings of pornography, senior scholars from across disciplines show the ways that sexuality became central to the individual, to the nation, and to the transnational character of modern society. The ten essays in the volume engage a rich array of topics, including obscenity in the German states, censorship in France's Third Republic, "she-male" internet porn
Introduction : issues and problems in the history of pornography / Lisa Z. Sigel -- Wanderers, entertainers and seducers : making sense of obscenity law in the German states, 1830-1851 / Sarah Leonard -- Censorship in republican times : censorship and pornographic novels located in L'enfer de La Bibliothèque Nationale, 1800-1900 / Annie Stora-Lamarre -- Anti-abolition writes obscenity: the English vice, transatlantic slavery, and England's obscene print culture / Colette Colligan -- The rise of the overly affectionate family : incestuous pornography and displaced desire among the Edwardian middle class / Lisa Z. Sigel -- Old wine in new bottles? : literary pornography in twentieth-century France / John Phillips -- A perfectly British business : stagnation, continuities, and change on the top shelf / Clarissa Smith -- Global traffic in pornography : the Hungarian example / Katalin Szoverfy Milter, Joseph W. Slade -- Ideologies of the second coming in the Ukrainian postcolonial playground / Maryna Romanets -- Stripping the nation bare : Russian pornography and the insistence on meaning / Eliot Borenstein -- "Walking on the wild side" : she-male internet pornography / John Phillips.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Pornography -- Europe; Pornography -- Europe -- History; Pornographie -- Europe; Pornographie -- Europe -- Histoire; SOCIAL SCIENCE -- Pornography; Pornography; Europe; Pornografie; Histoire; Pornographie; 19e siècle.; 20e siècle.; Europe; History